Neural Correlates of Inter-Trial Priming and Role-Reversal in Visual Search - Rorden, Chris; Kristjánsson, Árni; Revill, Kate P.; Saevarsson, Styrmir (Frontiers in Human Neuroscience, 2011)
Studies of priming of visual perception demonstrate that observers respond more quickly to targets in a field of distractors when relevant features are repeated versus novel or role-reversed. In a recent brain imaging study participants were presented with two items of one color and a single item in a different color with the task of reporting the orientation of the uniquely colored item. Consistent with previous behavioral reports, they found that observers were faster to respond when the target and distractor colors were identical to the previous trial than when they were reversed. They found reduced BOLD activity in brain areas linked with attentional control on trials where the target and distractor colors were repeated relative to reversed, which they interpreted as reflecting response suppression (decreased BOLD signal for repeated stimuli). However, since their design only compared repeated versus reversed task demands, it is logically possible that this pattern reflects increased BOLD signal for role-reversed stimuli: activity required to inhibit previously facilitated information and select previously inhibited information. We explored this possibility with a task where we contrasted the signal generated by repeated, reversed and novel features. Our data suggest that the majority of the change in neural signal elicited by priming of pop-out reflects increased activation when selection criteria are reversed.